The Independence of the Wali Nanggroe Institution from the Perspective of Asymmetric Decentralization - Itsnatul Mardhiyya; Husni Husni; M. Jafar (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2026)
The Wali Nanggroe Institution (WNI) is a distinctive institution of Aceh established as a consequence of the implementation of asymmetric decentralization through the granting of special autonomy status within the framework of the Unitary State of the Republic of Indonesia. Its existence is legally recognized under Law Number 11 of 2006 on the Governance of Aceh, which defines it as an independent customary leadership institution operating outside the formal structure of regional government. Nevertheless, the regulation of the Wali Nanggroe Institution under Aceh Qanun Number 2 of 2023 continues to raise legal concerns regarding its independence, functional boundaries, scope of authority, and institutional relationship with the Aceh Government. This study aims to examine the compatibility of the regulatory framework governing the Wali Nanggroe Institution with the principles of asymmetric decentralization and to assess the juridical implications of its existence, independence, and authority within Indonesia’s constitutional and regional governance system. Employing a normative juridical research method, the study adopts statutory, conceptual, and historical approaches through an extensive review of primary, secondary, and tertiary legal materials. The findings indicate that the regulatory framework of the Wali Nanggroe Institution generally conforms to the principles of asymmetric decentralization, as it reflects the State’s recognition of Aceh’s distinct historical, cultural, religious, and socio-political characteristics through the establishment of a unique institution endowed with special functions and powers. However, several normative issues remain unresolved, particularly concerning institutional independence, the delineation of functions, and the scope of authority, which may create overlaps with the competencies of the Aceh Government. The study further reveals that the Wali Nanggroe Institution possesses a sui generis character as a customary institution unique to Aceh, situated outside the formal structure of regional government while simultaneously playing a strategic role in safeguarding the implementation of Aceh’s special status and privileges. Accordingly, amendments to Aceh Qanun Number 2 of 2023 are necessary to provide clearer limitations on the institution’s functions, independence, and authority, thereby ensuring legal certainty, fostering harmonious institutional relations, and strengthening the implementation of asymmetric decentralization in accordance with the principles of the rule of law